Pensando a forma????o inicial em educa????o f??sica: entendendo o papel do est??gio em uma concep????o de a????o docente enquanto pr??xis - Sousa, Manuella Pereira de (2012)
The practicum activity contributes with the built process of teaching identity. The reflexion about the scholar reality, articulating the theory and the practices provides the learning and built the knowledge necessary for acting in the classroom. The perspective of practice rationality searches, during the initial upbringing teaching, to transform the classroom in a dialogue space and critics analysis. In this searching, the practicum activity was utilized like a reflection space, with the aim to reduce the gap between theory and practice in a perspective of teacher action as praxis. So, we seek to understand how the teacher reflects and analysis their own teaching action and how the reflection process helps to built knowledge and the teaching identity. The methodological reference that guided this study was a qualitative search in a constructive-collaborative model. The techniques to data collect used were: class diaries, focal groups, teaching cases and a questionnaire. We performed five focal groups during the second semester of 2010, in a Traineeship Supervised Discipline in Physical Education at Unesp. The data analysis indicated that the practicum activity, in a reflection perspective, was assed for the future teachers like positive. All participants in this search indicated that the experience contributed positively in the emergency of knowledge and learning and with the process to built the teaching identity. The strategies adopted in this search were considered positives and supported the reflection by the future teachers. The data suggested that the reflection process reduced the gap between theory and practices. We highlight as fundamental elements in this process: the critics and a reflective analysis occurred in the class diaries, as the collective obtained through the focal groups, the use of teaching cases in a moment of approach and reframing of reality and, the contact with theory discussions about the upbringing and teaching knowledge.